Promoting Healthy Relationships and Families: An Exploratory Study of the Perceptions of Resources and Information and Skill Needs Among Couples, Single Adults, and Parents. (July 2019) - Cannon, Jennifer L.; Murray, Christine E.
As there is growing awareness of the importance of healthy relationships among helping professionals and the general population, there is a need to gain a greater understanding of the types of supportive resources and services that can help people build and maintain healthy relationships across different areas of life. This article addresses the findings from an exploratory research study that utilized a mixed-methods approach to examine couples, single adults, and parents' perceptions of what resources are needed to promote healthy relationships and what barriers currently hinder them from seeking and obtaining such services. Results are discussed in context of the study's limitations, and implications for practice and future researchers are addressed.